The Impact of Beta Blockers on Survival in Heart Transplant Recipients: Insights from the Zabrze HTx Registry - Grzegorz M. Kubiak; Radosław Kwieciński; Agnieszka Ciarka; Andrzej Tukiendorf; Piotr Przybyłowski; Tomasz Hrapkowicz; Michał O. Zembala (Cardiology Research and Practice)
Introduction. The data assessing the impact of beta blocker (BB) medication on survival in patients after heart transplantation (HTx) are scarce and unequivocal; therefore, we investigated this population. Methods. We retrospectively analyzed the HTx Zabrze Registry of 380 consecutive patients who survived the 30-day postoperative period. Results. The percentage of patients from the entire cohort taking BBs was as follows: atenolol 24 (17%), bisoprolol 67 (49%), carvedilol 11 (8%), metoprolol 28 (20%), and nebivolol 8 (6%). The patients receiving BBs were older (56.94 ± 14.68 years vs. 52.70 ± 15.35 years, p=0.008) and experienced an onset of HTx earlier in years (11.65 ± 7.04 vs. 7.24 ± 5.78 p≤0.001). They also had higher hematocrit (0.40 ± 0.05 vs. 0.39 ± 0.05, p=0.022) and red blood cells (4.63 (106/μl) ± 0.71 vs. 4.45 (106/μl) ± 0.68, p=0.015). Survival according to BB medication did not differ among the groups (p=0.655) (log-rank test). Univariate Cox proportional hazard regression analysis revealed that the following parameters were associated with unfavorable diagnosis: serum concentration of albumin (g/l) HR: 0.87, 95% CI (0.81–0.94), p=0.0004; fibrinogen (mg/dl) HR: 1.006, 95% CI (1.002–1.008), p=0.0017; and C-reactive protein (mg/l) HR: 1.014, 95% CI (1.004–1.023), p=0.0044. Conclusions. The use of BBs in our cohort of patients after HTx was not associated with survival benefits.